2023
DOI: 10.1111/jon.13094
|View full text |Cite
|
Sign up to set email alerts
|

Improved cochlear implant electrode localization using coregistration of pre‐ and postoperative CT

Abstract: Background and Purpose Artifact from cochlear implant electrodes degrades image resolution on CT. Here, we describe the use of coregistered pre‐ and postoperative CT images to reduce metallic artifact from the electrodes to assess its position more accurately within the cochlear lumen. Methods Pre‐ and postoperative CTs were reviewed after coregistration/overlay of both exams. Images were evaluated by two neuroradiologists for scalar location of electrodes tip (± scalar translocation), tip fold over, and angul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For scalar translocation detection of the complete electrode array, Jia et al (29) reported agreement between expert judgments on intraoperative cone beam CT to be as low as 43 to 53%. Farnsworth et al (13) found Cohen's κ of 0.78 for translocation agreement between experts in a relatively small study with three translocations in 34 patients. This means that differences between manual and semiautomatic scalar position assessments in our study are not necessarily errors from the tools, but could also be due to interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For scalar translocation detection of the complete electrode array, Jia et al (29) reported agreement between expert judgments on intraoperative cone beam CT to be as low as 43 to 53%. Farnsworth et al (13) found Cohen's κ of 0.78 for translocation agreement between experts in a relatively small study with three translocations in 34 patients. This means that differences between manual and semiautomatic scalar position assessments in our study are not necessarily errors from the tools, but could also be due to interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…Because the contacts of a lateral wall array are located further away from the modiolar axis, a certain absolute localization difference will lead to a smaller difference in AID compared with precurved arrays. For example, one study found an interobserver ICC of 0.96 for manual AID measurement of straight arrays (28), whereas another found an ICC of 0.67 for patients implanted with a precurved array (13). Our results show that the tool leads to consistent AID measurements that are comparable to manual measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation